Relationship between Knowledge and Anxiety in Covid-19 Patients in the Shafa Marwa Isolation Room of Medan Haji Hospital in 2021 - Muslimah Pase (Science Midwifery, 2021)
Coronaavirus (Cov) is a family of viruses that causes various diseases, from the common cold to more serious illnesses. SARS CoV-2, the name of the virus that causes the disease known as COVID-19, is a new type of coronavirus, this virus has not been previously identified in humans. Corona viruses are zoonotic, which means they are transmitted from animals to humans. One way to reduce anxiety levels in Covid-19 patients is by providing knowledge. This study aims to determine the relationship between knowledge and anxiety in covid-19 patients in the isolation room of Shafa Marwa Hospital of Haji Medan in 2021. This study used a descriptive correlation type with a cross sectional approach. The total population of the researchers was 70 people. The sampling technique was carried out by accidental sampling technique so that the sample size was 30 people. Power analysis used Spearman's Rho test. The results of the study using the Spearman`s Rho correlation test were obtained p = 0.000 <α 0.05. This shows that there is a relationship between knowledge and anxiety in covid-19 patients in the Shafa Marwa room of the Medan Hajj Hospital in 2021. The conclusion is that there is a relationship between knowledge and anxiety in Covid-19 patients in the Shafa Marwa room of the Medan Haji Hospital. It is hoped that nurses pay more attention to aspects of knowledge in Covid-19 patients to prevent anxiety in isolation rooms. This shows that there is a relationship between knowledge and anxiety in covid-19 patients in the Shafa Marwa room of the Medan Hajj Hospital in 2021. The conclusion is that there is a relationship between knowledge and anxiety in Covid-19 patients in the Shafa Marwa room of the Medan Haji Hospital. It is hoped that nurses pay more attention to aspects of knowledge in Covid-19 patients to prevent anxiety in isolation rooms. This shows that there is a relationship between knowledge and anxiety in covid-19 patients in the Shafa Marwa room of the Medan Hajj Hospital in 2021. The conclusion is that there is a relationship between knowledge and anxiety in Covid-19 patients in the Shafa Marwa room of the Medan Haji Hospital. It is hoped that nurses pay more attention to aspects of knowledge in Covid-19 patients to prevent anxiety in isolation rooms.